PRESS RELEASE The fairness of ethical decisions related to the allocation of medical resources within the COVID-19 pandemic - Lazić, Aleksandra; Zlatko (Journal Resuscitatio Balcanica, 2020)
The Serbian Resuscitation Council discussed, considered, and adopted based on the National Course Director opinion leaders consensus in the field of resuscitation medicine about the basic principles of resource allocations, related to the application of resuscitation procedures and care of patients during the pandemics, The COVID-19 pandemic around the world has brought a lot of changes within all segments of life, we all are faced to everyday challenges, including ethics in medicine, which is a very sensitive area due to specifics that are unique and different in each country individually, with strong cultural, economic, religious, medical, legal, and other diversities. The challenges are enormous, given by the current lack of a specific therapy, by the limited resources available for diagnosis, intervention, and preventive measures. The pandemic also brought the need to create conditions for the application of "unusual" requirements, measures, and procedures of the healthcare system and medical care, which entails a certain reorganization of medical interventions and care systems, including mandatory personal protection measures, adherence to adequate social distance, and all hygienic procedures. General ethical principles, such as maximum benefit and equality of treatment, while giving priority to those with the most severe conditions, have created the need to create ethical recommendations related to the allocation of medical resources in the COVID-19 pandemic and Eziekel et al. published six principles related to the above in terms of maximizing benefits, giving an advantage to healthcare professionals, triage outside the framework of the "first arrival" basis, responding to findings, recognizing participation in research, and applying the same principles to COVID-19 and in non-COVID-19 patients. A fair allocation of these ethical values ​​and principles requires adaptable ethical frameworks depending on the resources available and the organizational structure of the healthcare system.